2-Alkyl substituted benzimidazoles as a new class of selective AT2 receptor ligands. (15th July 2022) - Roy, Tamal; Petersen, Nadia N.; Gopalan, Greeshma; Gising, Johan; Hallberg, Mathias; Larhed, Mats
Graphical abstract: Abstract: Ligands comprising a benzimidazole rather than the imidazole ring that is common in AT2 R ligands e.g. in the AT2 R agonist C21, can provide both high affinity and receptor selectivity. In particular, compounds encompassing benzimidazoles, substituted in the 2-position with small bulky groups such as an isopropyl ( K i  = 4.0 nM) or a tert -butyl ( K i  = 5.3 nM) or alternatively a thiazole heterocycle ( K i  = 5.1 nM) demonstrate high affinity and AT2 R selectivity. An n -butyl chain, as found in the AT1 R selective sartans, makes the ligand less receptor selective. The isobutyl group on the biaryl scaffold present in most AT2 R selective ligands reported so far was originally derived from the nonselective potent AT1 R/AT2 R ligand L-162, 313. Notably, in all ligands discussed herein, the isobutyl group was substituted by an n -propyl group and ligands with high affinity to AT2 R were provided and in addition the majority of them demonstrate a favorable AT2 R/AT1 R selectivity. The introduction of fluoro atoms in various positions had no pronounced effect on the affinity data. Ligands with a thiazole or a tert -butyl group attached to the 2-position and with a terminal trifluoromethyl butoxycarbonyl sidechain exhibited a similar stability as C21 in human liver microsomes, while other ligands examined were less stable in the microsome assay.